2004
DOI: 10.1074/jbc.m405770200
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Catalytic Subunit of Protein Phosphatase 2A Impairs Cardiac Function

Abstract: Reversible protein phosphorylation is an essential regulatory mechanism in many cellular functions. In contrast to protein kinases, the role and regulation of protein phosphatases has remained ambiguous. To address this issue, we generated transgenic mice that overexpress the catalytic subunit ␣ of protein phosphatase 2A (PP2A) (PP2Ac␣) in the heart driven by the ␣-myosin heavy chain promoter. Overexpression of the PP2Ac␣ gene in the heart led to increased levels of the transgene both at RNA and protein levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
154
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(173 citation statements)
references
References 43 publications
17
154
0
2
Order By: Relevance
“…Although overexpression of PP2Ac in a transgenic mouse led to upregulation of PP2Ac enzymatic activity (44), mutation of the catalytic site leads to increased expression of PP2A protein (45). Since phosphorylation of PP2Ac inhibits its catalytic activity (46) and SLE T cells display increased TCR/CD3-initiated phosphorylation of cytosolic proteins (47), we considered the increased protein levels of PP2Ac may represent a compensatory response to improperly phosphorylated and therefore inactive PP2Ac (46).…”
Section: Resultsmentioning
confidence: 99%
“…Although overexpression of PP2Ac in a transgenic mouse led to upregulation of PP2Ac enzymatic activity (44), mutation of the catalytic site leads to increased expression of PP2A protein (45). Since phosphorylation of PP2Ac inhibits its catalytic activity (46) and SLE T cells display increased TCR/CD3-initiated phosphorylation of cytosolic proteins (47), we considered the increased protein levels of PP2Ac may represent a compensatory response to improperly phosphorylated and therefore inactive PP2Ac (46).…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggest the obscurin-ankyrin-B complex is necessary for recruitment of PP2A to the Mband. PP2A, a major protein phosphatase in the heart, is responsible for modulating Ca 2+ signaling through its regulation of essential ion channels and pumps (Gergs et al 2004;Lei et al 2015Lei et al , 2016. Aberrant expression or mislocalization of PP2A is associated with cardiac pathophysiology, including heart failure and arrhythmias (Gergs et al 2004;Lei et al 2015;Li et al 2016).…”
Section: Obscurins Function As Signaling Mediators At M-bandsmentioning
confidence: 99%
“…PP2A, a major protein phosphatase in the heart, is responsible for modulating Ca 2+ signaling through its regulation of essential ion channels and pumps (Gergs et al 2004;Lei et al 2015Lei et al , 2016. Aberrant expression or mislocalization of PP2A is associated with cardiac pathophysiology, including heart failure and arrhythmias (Gergs et al 2004;Lei et al 2015;Li et al 2016). In addition, in C. elegans the protein phosphatase SCPL-1, which localizes to the M-band, interacts with the pseudo-kinase regions of UNC-89 (Qadota et al 2008b;Xiong et al 2009).…”
Section: Obscurins Function As Signaling Mediators At M-bandsmentioning
confidence: 99%
“…Truttmann et al (2004) demonstrated that hypoxia decreased catalytic activity and protein levels of the PP2 catalytic subunit in cerebral cortex of newborn piglets. Gergs et al, (2004) generated transgenic mice with tissue specific over-expression of the catalytic subunit alpha (PP2acaAlpha) in the heart. Over-expression led to tissue necrosis and fibrosis and altered phosphorylation of a number of PP2 target proteins.…”
Section: Ppp2r1a and Phosphatase 2 (Pp2)mentioning
confidence: 99%